Microbiological Stability of Fermented Chicken Meat Spread Under Refrigerated (4±1ºC) Storage - Agrawal, Namrata; Singh, Pradeep Kumar; Yadav, Surbhi; Gupta, Swati; Singh, Ranvijay; Gupta, Bhavana (Indian Journal of Veterinary Sciences and Biotechnology, 2024)
Chicken meat spread was prepared with malted sorghum flour as substrate and Lactobacillus acidophilus (LAB) @ 1 million CFU/g as  a fermenting probiotic organism. The products were stored under refrigeration (4±1ºC) up to 16 days for microbial stability. Different  formulations were evaluated: C (meat spread only, control), C1 (meat spread + LAB), T1 (meat spread with 2% malted sorghum flour +  LAB), T2 (meat spread with 4% malted sorghum flour + LAB), and T3 (meat spread with 6% malted sorghum flour + LAB). The products  were microbiologically stable during the study period of 16 days. Total plate count and Yeast and mold count increased significantly  (p≤0.05) towards the end of the storage period; however, the values were within the safe limits for the meat products. Coliforms were  absent during the entire storage study. The count of Lactobacillus acidophilus, observed in T2 and T3 on 0 day suggests that considering  the serving size of product as 100 g per day the required minimum number of viable probiotic organism was ≥108 CFU prescribed for  a probiotic product.
Keywords: Chicken meat spread,; Fermented product; Lactobacillus acidophilus,; Probiotics,; Sorghum flour.